IDENTIFIKASI Brucella abortus DARI BUFFY COAT DARAH SAPI YANG TERDUGA BRUCELLOSIS DI KABUPATEN LAMPUNG SELATAN DAN KLATEN DENGAN METODE POLYMERASE CHAIN REACTION (PCR) DAN FILOGENI ISOLAT BAKTERI YANG BERASAL DARI BEBERAPA DAERAH DI INDONESIA - , Vera Duana Ambya; , Prof. drh. Kurniasih, M.VSc., Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Brucellosis was a zoonotic diseases giving a risk to the health of human and animal. The disease became national priority for preventing, controlling and eradication in Indonesia. Molecular analysis with Polymerase Chain Reaction (PCR) method has been used for bacterial diagnosis and genetic variation. Bacteria was intracellular facultative so that could stay within phagocytic and no phagocytic celullars. Objective of study was to identify B. abortus from buffy coat of cattle blood with PCR method and genetic variation of bacterial isolates from several areas in Indonesia. Blood buffy coat of cattle was originated from South Lampung and Klaten with eight samples of each areas, and four isolate of B. abortus from several areas in Indonesia. Research was supported by serological test of Rose Bengal Test (RBT) and complement Fixation Test (CFT). Molecular examination consist of DNA extraction using Qiagen QIAmp DNA mini kit, amplification in Omp2b gen using forward primer: 5-GGTCAGCATAA AAAGCAAGC-3 and reverse primer: 5-CCTTCAGCCAAATCAGAATG-3, electrophoresis, and DNA sequencing. Four cattle were positive of RBT and CFT test from sixteen number of cattle. Result of PCR from blood buffy coat of cattle that symptomatic brucellosis. Phylogeny of four bacterial isolates showed that they were close related, even though its validity was low (60%). Identification of B. abortus from blood buffy coat of cattle was not recommended except from acute condition of brucellosis.